KARAKTERISTIK DAN PERMASALAHAN UNTUK ANAK BERKEBUTUHAN KHUSUS - Nurwidyayanti Nurwidyayanti (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Children with special needs (ABK) are children with special characteristics that are different from children in general without always showing mental, emotional or physical disabilities. Children with special needs are children who experience significant abnormalities/deviations (physical, mental-intellectual, social, and emotional) in their growth and development process compared to other children of the same age so that they require special education services. Children with Special Needs (ABK) is another term to replace the word